Over-Generalizing About GC (Hypoxia): Pitfalls of Limiting Breadth of Experimental Systems and Analyses in Framing Informatics Conclusions - Boothby, Mark R.; Raybuck, Ariel; Cho, Sung Hoon; Stengel, Kristy R.; Haase, Volker H.; Hiebert, Scott; Li, Jingxin (Frontiers in Immunology, 2021)
Accumulating evidence suggests that immune responses are influenced by local nutrient concentrations, in addition to the programming of intermediary metabolism within immune cells. Humoral immunity and germinal centers (GC) are settings in which these factors are under active investigation. Hypoxia is one example of how a particular nutrient is distributed in lymphoid follicles during an antibody response, and how oxygen sensors can impact the qualities of antibody output after immunization. Using a bio-informatic analysis of mRNA levels in GC and other B cells, recently published work challenges the concepts that there is any hypoxia or that it has any influence. We have performed new analyses of published genomics data to explore potential sources of disparity and elucidate aspects of what might seem to be conflicting conclusions. In particular, replicability and variance among data sets derived from different naïve as well as GC B cells are considered. The results highlight several broader issues that merit consideration, especially at a time of heightened focus on scientific reports in the realm of immunity and antibody responses. Based on these analyses, a standard is proposed under which the relationship of new data sets should be compared to prior “fingerprints” of cell types and reported transparently to referees and readers. In light of the strong evidence of diversity within and among GC elicited by protein immunization, another core practice should be to avoid overly broad conclusions about germinal centers in general when experimental systems are subject to substantial constraints imposed by technical features.